2004
DOI: 10.1002/maco.200403795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BEASY program using linear and piecewise linear approaches for the boundary conditions

Abstract: The boundary element method (BEM) was used to study galvanic corrosion using linear and logarithmic boundary conditions. The linear boundary condition was implemented by using the linear approach and the piecewise linear approach. The logarithmic boundary condition was implemented by the piecewise linear approach. The calculated potential and current density distribution were compared with the prior analytical results. For the linear boundary condition, the BEASY program using the linear approach and the piece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…[43] Adey [39] stated that BEM was suitable for modeling corrosion, and that computer simulation of galvanic corrosion could be undertaken with confidence with commercial programs like BEASY. Our preliminary research [44] showed that the BEM program BEASY provided calculated values in agreement with analytical approaches and FEM calculations. Most of the previous studies have also reported agreement between modeling predictions and experimental measurements for the galvanic current distribution.…”
mentioning
confidence: 71%
“…[43] Adey [39] stated that BEM was suitable for modeling corrosion, and that computer simulation of galvanic corrosion could be undertaken with confidence with commercial programs like BEASY. Our preliminary research [44] showed that the BEM program BEASY provided calculated values in agreement with analytical approaches and FEM calculations. Most of the previous studies have also reported agreement between modeling predictions and experimental measurements for the galvanic current distribution.…”
mentioning
confidence: 71%
“…Recent research [5,20,21,22,26,29,30] has investigated the influence of geometric factors on the galvanic current distribution for AZ91D coupled to steel using a Boundary Element Method (BEM) model and experimental measurements. The experimental measurements used a multi-channel zero resistance ammeter and an idealized 1D galvanic corrosion assembly.…”
Section: Galvanic Corrosionmentioning
confidence: 99%
“…Petty et al [18] interpreted their experiments as showing that the first step in the anodic oxidation of Mg was the unipositive ion Mg + , produced by means of Mg = Mg + + e (10) and that this Mg + ion could be further oxidized electrochemically to the stable species Mg ++ by:…”
Section: Existence Of the Unipositive Magnesium Ionmentioning
confidence: 99%
“…This interest is warranted by the fact that the NDE is of central importance to the corrosion of magnesium, [2][3][4][5] including galvanic corrosion [6][7][8][9][10] and stress corrosion cracking. [11][12][13][14][15] The NDE is also probably an issue for magnesium anodes used in cathodic protection, (see e.g.…”
mentioning
confidence: 99%